2021
DOI: 10.3389/fcell.2021.671838
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Deregulation of the Histone Methyltransferase KMT5B Contributes to Malignant Transformation in Glioblastoma

Abstract: Glioblastoma multiforme (GBM) is the most common and aggressive type of brain tumor in adulthood. Epigenetic mechanisms are known to play a key role in GBM although the involvement of histone methyltransferase KMT5B and its mark H4K20me2 has remained largely unexplored. The present study shows that DNA hypermethylation and loss of DNA hydroxymethylation is associated with KMT5B downregulation and genome-wide reduction of H4K20me2 levels in a set of human GBM samples and cell lines as compared with non-tumoral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 69 publications
1
6
0
Order By: Relevance
“…found that the changes in gene expression of various methyltransferases, acetyltransferases, and deacetylases promoted the pathogenesis of GBM 189 . The nuclear expression levels of lysine methyltransferases SETDB1, KMT5B, Suv‐39h1, and EZH2 in GBM are up‐regulated, compared with normal tissues, and correlated with advanced histological grades 190–193 . Besides, the inhibition of LSD1 in GBM has been discovered by Chandra et al.…”
Section: Abnormal Expression Of Histone‐modifying Enzymes and Human C...mentioning
confidence: 91%
See 1 more Smart Citation
“…found that the changes in gene expression of various methyltransferases, acetyltransferases, and deacetylases promoted the pathogenesis of GBM 189 . The nuclear expression levels of lysine methyltransferases SETDB1, KMT5B, Suv‐39h1, and EZH2 in GBM are up‐regulated, compared with normal tissues, and correlated with advanced histological grades 190–193 . Besides, the inhibition of LSD1 in GBM has been discovered by Chandra et al.…”
Section: Abnormal Expression Of Histone‐modifying Enzymes and Human C...mentioning
confidence: 91%
“…189 The nuclear expression levels of lysine methyltransferases SETDB1, KMT5B, Suv-39h1, and EZH2 in GBM are upregulated, compared with normal tissues, and correlated with advanced histological grades. [190][191][192][193] Besides, the inhibition of LSD1 in GBM has been discovered by Chandra et al to sensitize cells to HDACIs, so LSD1 and HDAC can work together to regulate cell death in GBM cell lines. 194 Besides, patients with higher KDM5B levels in GBM usually have poorer overall survival rates and can promote cancer cell proliferation by regulating p21 expression.…”
Section: Glioblastoma (Gbm)mentioning
confidence: 99%
“…Frequently in cancer, including GBM [ 120 ], there is abnormal methylation level at lysine 20 of histone H4 (H4K20me) [ 121 ].…”
Section: Epigenetic Changes In Aging-related Diseasesmentioning
confidence: 99%
“…Studies of genome-wide disclosed that the gene encoding the histone methyltransferase KMT5B (alias SUV420H1) presents frequently hypermethylated and hypo-hydroxymethylated of DNA in GBM [ 121 , 122 ].…”
Section: Epigenetic Changes In Aging-related Diseasesmentioning
confidence: 99%
See 1 more Smart Citation